Fermented healing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Here s a tip for healthy eating (and healthy sales if you grow soya). Fermented soya (tempeh) can reduce the duration and severity of diarrhoea, by preventing E. coli bacteria notorious for causing diarrhoea - from attaching to the intestines....